Diagnostic utility of LMO2 immunohistochemistry in distinguishing T-lymphoblastic leukemia/lymphoma from thymoma - Bansal, Divya; Pasricha, Sunil; Gupta, Gurudutt; Sharma, Anila; Durga, Garima; Kamboj, Meenakshi; Mehta, Anurag (Indian journal of pathology & microbiology, 2024)
ABSTRACT Distinguishing T-lymphoblastic leukemia/lymphoma (T-ALL/T-LBL) from thymomas (especially B1 or B2 type) can be challenging particularly in limited trucut biopsy material where appreciating architecture is difficult or the background epithelial component does not provide tangible evidence for definite diagnosis. As a pathologist, it is important to accurately diagnose these neoplasms because they have entirely distinct management protocols. Recent studies have reported that LIM Domain Only 2 (LMO2) is expressed in neoplastic lymphoblasts of T-ALL/T-LBL and is absent in thymocytes of normal thymuses or thymomas. An observational study was done to test the sensitivity and specificity of LMO2 in differentiating neoplastic lymphoblasts from thymocytes of thymomas/normal thymuses. Our study showed that LMO2 had sensitivity of 70% and specificity of 100% in diagnosing LBL. None of the thymomas (B1 or B2 type) showed expression of LMO2 in the neoplastic cells. LMO2 is a reliable marker of transformed T-cell precursors and should be routinely included in immunohistochemical panel when evaluating thymic/mediastinal neoplasms.